INDMET: An industrial oriented softcopy photogrammetric system - Lichti, Derek; Chapman, M.; Cosandier, D. (Canadian Institute of Geomatics, 1995)
In many instances, photogrammetry may be considered advantageous over other deformation monitoring techniques as it is a non-contact method of remote measurement which also yeilds a visual record (i.e. the imagery) of the area being monitored. Softcopy photogrammetry offers many advantages over conventional hardcopy approaches since the imagery is available in a computer compatible form. In terms of data processing, the capabilities of fast data capture, automatic image point recognition and measurement and real-time or near real-time data reduction permits a flexible image measurement approach. A close-range softcopy photogrammetric system for industrial machinery deformation monitoring has been developed by the Department of Geomatics Engineering at The University of Calgary. This paper presents an overview of the hardware and software development of this system. The mathematical models used for target measurement and photogrammetric estimation as well as system calibration and network design are detailed. Applications of this system are also presented. Finally, an overview of current system developments is given.